2014
DOI: 10.1007/s11274-014-1610-7
|View full text |Cite
|
Sign up to set email alerts
|

NADH: flavin oxidoreductase/NADH oxidase and ROS regulate microsclerotium development in Nomuraea rileyi

Abstract: Based on transcriptome library, an NADH: flavinoxidore ductase/NADH oxidase gene (Nox) was cloned from Nomuraea rileyi. The 1,663-bp full-length cDNA contains an open reading frame of 1,233 bp coding 410 amino acids. The expression level of Nox was up-regulated and co-related to the intracellular H2O2 concentration during microsclerotium (MS) initiation. Rotenone inhibition showed that inhibition of Nox could cause a noticeable decrease in the MS yields. Silencing of Nox resulted in the MS yields, H2O2 and vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…The M. rileyi strain, CQNr01, was obtained from the Chongqing Engineering Research Center for Fungal Insecticides, Chongqing, China. The strain had been used to study the optimisation of culture medium for MS production (Yin et al 2012;Song et al 2014a) and study the molecular mechanism of MS development in our earlier research (Song et al 2013(Song et al , 2016aJiang et al 2014;Liu et al 2014;Zhou et al 2015). The strain was cultured on Sabouraud's maltose agar fortified with 1% yeast extract (SMAY) under continuous light at 25°C.…”
Section: Strain and Inoculum Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The M. rileyi strain, CQNr01, was obtained from the Chongqing Engineering Research Center for Fungal Insecticides, Chongqing, China. The strain had been used to study the optimisation of culture medium for MS production (Yin et al 2012;Song et al 2014a) and study the molecular mechanism of MS development in our earlier research (Song et al 2013(Song et al , 2016aJiang et al 2014;Liu et al 2014;Zhou et al 2015). The strain was cultured on Sabouraud's maltose agar fortified with 1% yeast extract (SMAY) under continuous light at 25°C.…”
Section: Strain and Inoculum Preparationmentioning
confidence: 99%
“…For the development of efficient fermentation, the culture conditions and liquid culture fermentation process should be optimised owing to their impact on the M. rileyi MS yields. Optimisation studies could also help in understanding the interactions among the parameters as well as the mechanism of MS development (Song et al 2013(Song et al , 2016aJiang et al 2014;Liu et al 2014;Zhou et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the fermentation efficiency, we investigated the molecular mechanism of MS formation and found that internal oxidative stress could trigger MS differentiation910. We additionally investigated the role of regulatory components in H 2 O 2 production and hypal polarized growth1112.…”
mentioning
confidence: 99%
“…Cells were harvested by centrifugation at 4000 g , 4°C for 5 min, resuspended in the same volume of precooled deionized water. Intracellular H 2 O 2 was released by sonicating on ice, measured using a hydrogen peroxide assay kit (Beyotime, Nantong, Jiangsu, China) (Liu et al, ), and normalized against the cytoplasmic volume using a standard ratio of 0.47 µL of internal volume per 1 mL of E. coli culture with OD 600 of 1.0 (Imlay and Fridovich, ).…”
Section: Methodsmentioning
confidence: 99%